Behaviour of salt affected soil with different electrolyte concentration - Chakraborty, Bhargabi (Indian Farming, 2018)
A major concern in irrigated agriculture is the maintenance of sufficiently high soil permeability for salinity control. It is well known that the concentration and composition of the percolating solution has a great influence on the stability of soil structure and hydraulic conductivity with decreasing electrolyte concentration and increasing SAR of the percolating solution. A satisfactory permeability could be maintained even at higher levels of ESP by maintaining the electrolyte concentration of the percolating water.